ODYSSEY COMBO II: Alirocumab Significantly Improves Cholesterol Levels in Patients with High CV Risk - Parry, Nicola (MD Conference Express, 2014)
This articls presented results from the Efficacy and Safety of Alirocumab (SAR236553/REGN727) Versus Ezetimibe on Top of Statin in High Cardiovascular Risk Patients With Hypercholesterolemia trial [ODYSSEY COMBO II; NCT01644188]. This phase 3 trial showed that for patients with high cholesterol and existing or increased risk of cardiovascular disease, alirocumab significantly improved cholesterol levels as compared to ezetimibe, when added to regular statin therapy.